Collaboration for Strategic Change: Examining Dialectical Tensions in an Interorganizational Change Effort. (August 2019) - Hoelscher, Carrisa S.
Given the increasing number of interorganizational collaborations across governmental and private sectors, this study furthers theoretical understanding of these relationships by focusing on dialectical tensions experienced in a collaborative strategic change effort. The research site was an 11-member statewide interorganizational committee working to create change across all involved organizations. Data collection included prolonged observation of meetings over 18 months and interviews with committee leaders. Analytical procedures began with a modified constant comparative analysis that guided the research toward a tension-centered approach for ongoing data collection and analysis. Results include seven dialectical tensions representing three tension types: commitment-based, process-based, and outcome-based tensions. Participants used four strategies for communicatively negotiating tensions: acknowledging, delaying, hedging, and invoking authoritative texts. This study contributes to an increasing awareness of the constitutive nature of communication in collaborations and continues to refine our understanding of dialectical tension management in group interactions.